Crosstalk between the HpArsRS two-component system and HpNikR is necessary for maximal activation of urease transcription - Carpenter, Beth M.; West, Abby L.; Gancz, Hanan; Servetas, Stephanie L.; Pich, Oscar Q.; Gilbreath, Jeremy J.; Hallinger, Daniel R.; Forsyth, Mark H.; Merrell, D. Scott; Michel, Sarah L. J. (Frontiers in Microbiology, 2015)
Helicobacter pylori NikR (HpNikR) is a nickel dependent transcription factor that directly regulates a number of genes in this important gastric pathogen. One key gene that is regulated by HpNikR is ureA, which encodes for the urease enzyme. In vitro DNA binding studies of HpNikR with the ureA promoter (PureA) previously identified a recognition site that is required for high affinity protein/DNA binding. As a means to determine the in vivo significance of this recognition site and to identify the key DNA sequence determinants required for ureA transcription, herein, we have translated these in vitro results to analysis directly within H. pylori. Using a series of GFP reporter constructs in which the PureA DNA target was altered, in combination with mutant H. pylori strains deficient in key regulatory proteins, we confirmed the importance of the previously identified HpNikR recognition sequence for HpNikR-dependent ureA transcription. Moreover, we identified a second factor, the HpArsRS two-component system that was required for maximum transcription of ureA. While HpArsRS is known to regulate ureA in response to acid shock, it was previously thought to function independently of HpNikR and to have no role at neutral pH. However, our qPCR analysis of ureA expression in wildtype, ΔnikR and ΔarsS single mutants as well as a ΔarsS/nikR double mutant strain background showed reduced basal level expression of ureA when arsS was absent. Additionally, we determined that both HpNikR and HpArsRS were necessary for maximal expression of ureA under nickel, low pH and combined nickel and low pH stresses. In vitro studies of HpArsR-P with the PureA DNA target using florescence anisotropy confirmed a direct protein/DNA binding interaction. Together, these data support a model in which HpArsRS and HpNikR cooperatively interact to regulate ureA transcription under various environmental conditions. This is the first time that direct “cross-talk” between HpArsRS and HpNikR at neutral pH has been demonstrated.